An Analysis of the Qualitative Characteristics of Management Commentary Reporting by New Zealand Companies - Bikram Chatterjee; Stuart Tooley; Vic Fatseas; Alistair Brown (Australasian Accounting, Business and Finance Journal, 2012)
The narrative section of annual reports has considerable value to its user groups, such as financial analysts and investors (Barlett & Chandler 1997; International Accounting Standards Board (IASB) 2006; Tiexiera 2004). This narrative section including chairpersons’/presidents’ statement contains twice the quantity of information than the financial statements section (Smith & Taffler 2000). However, the abundance of information does not necessarily enhance the quality of such information (IASB 2006). This issue of qualitative characteristics has been long foregone by researchers. This issue has attracted the attention of IASB (2006). Following the dearth in research in regard to qualitative characteristics of reporting this paper explores whether investors’ required qualitative characteristics as outlined by the IASB (2006) have been satisfied in the management commentary section of New Zealand companies’ annual reports. Our result suggests that the principal stakeholders’, that is, investors’ qualitative characteristics requirements have been partially met in this section of annual reports. The qualitative characteristic of ‘relevance’ and ‘supportability’ have been satisfied in more annual reports compared to that of ‘balance’ and ‘comparability’.
Keywords: Management commentary; New Zealand companies; qualitative characteristics